The Relationship between Risk and Firm Performance of Listed Companies in Thailand - Promsen, Waewdao (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This study aims to examine the relationship between risk and firm performance of listed companies on the Stock Exchange of Thailand. The sample size consists of 1,503 firm-year over the period 2015 - 2018. Firm performance measurement consist of accounting - based and market -based. For market – based was measured by Enterprise Value and Market to Book Ratio, accounting - based was measured by Return on Asset and Return on Equity. The correlation analysis and multiple regression analysis were used for data analysis. The results indicated that risk had positive effects on firm performance for both accounting – based and market – based.